COMPARATIVE ANALYSIS OF SUSTAINABLE MICRO AND NANO MATERIALS DERIVED FROM PLANT EXTRACT AND MICROBIAL STRAIN PRECURSOR - Modi, Prabha; Vasava, Rutu; Joshi, Preeti (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study presents thorough comparative analysis of sustainable micro and nano materials derived from plant extracts and microbial strain precursors, showcasing the transformative potential of Green Chemistry in nanomaterial production. By assessing the efficiency , yield and environmental impact of key precursors – such as Neem and Moringa leaf extracts, along with microbial strains like rochei and Bacillus subtilis. The research emphasis on the advantages of bio-based methods over traditional chemical approaches. A systematic optimization of the precursor concentration along with the synthesis parameters and phytochemical profiling, effective strategies were designed for enhancing the nanoparticle yield and its quality, reducing the ecological impact. The use of advanced characterization and sustainability indicators were incorporated highlighting the potential of different green pathways for scalable, eco-friendly nanotechnology. The survey not only contributes to scientific knowledge but also creates a stage for innovative, sustainable solutions in material science and environmental engineering.